Chitosan treatment reduces softening and chilling injury in cold-stored Hami melon by regulating starch and sucrose metabolism - Zhang, Qin; Tang, Fengxian; Cai, Wenchao; Peng, Bo; Ning, Ming; Shan, Chunhui; Yang, Xinquan (Frontiers in Plant Science, 2022)
Cold-stored Hami melon is susceptible to chilling injury, resulting in quality deterioration and marketability reduction. Pre-storage treatment with chitosan reduces fruit softening and chilling injury in melon; however, the underlying mechanism remains unclear. In this study, Gold Queen Hami melons were treated with 1.5% chitosan solution for 10 min before cold storage at 3 ℃ and then the effect of chitosan was examined on fruit firmness, weight loss, chilling injury, and soluble solid content (SSC), pectin, and soluble sugar contents of melon fruit. Also, the enzyme activities and gene expression related to fruit softening and starch and sucrose metabolism were investigated. Chitosan treatment reduced fruit softening and chilling injury, maintained the high levels of starch and sucrose contents, and regulated the enzyme activities and gene expressions related to starch and sucrose metabolism. Fruit firmness was significantly positively correlated with sucrose and starch contents. Altogether, we uncovered the possible mechanism of chitosan coating mitigating melon softening and chilling injury by regulating starch and sucrose metabolism.